Microbial Degradation of Indole and Its Derivatives - Pankaj Kumar Arora; Ashutosh Sharma; Hanhong Bae (Journal of Chemistry)
Indole and its derivatives, including 3-methylindole and 4-chloroindole, are environmental pollutants that are present worldwide. Microbial degradation of indole and its derivatives can occur in several aerobic and anaerobic pathways; these pathways involve different known and characterized genes. In this minireview, we summarize and explain the microbial degradation of indole, indole-3-acetic acid, 4-chloroindole, and methylindole.